Targeting Angiogenesis in Cancer Therapy: Moving Beyond Vascular Endothelial Growth Factor - Zhao, Yujie; Adjei, Alex A. (The oncologist (Dayton, Ohio), 2015)
Angiogenesis, or the formation of new capillary blood vessels, occurs primarily during human development and reproduction; however, aberrant regulation of angiogenesis is also a fundamental process found in several pathologic conditions, including cancer. As a process required for invasion and metastasis, tumor angiogenesis constitutes an important point of control of cancer progression. Although not yet completely understood, the complex process of tumor angiogenesis involves highly regulated orchestration of multiple signaling pathways. The proangiogenic signaling molecule vascular endothelial growth factor (VEGF) and its cognate receptor (VEGF receptor 2 [VEGFR‐2]) play a central role in angiogenesis and often are highly expressed in human cancers, and initial clinical efforts to develop antiangiogenic treatments focused largely on inhibiting VEGF/VEGFR signaling. Such approaches, however, often lead to transient responses and further disease progression because angiogenesis is regulated by multiple pathways that are able to compensate for each other when single pathways are inhibited. The platelet‐derived growth factor (PDGF) and PDGF receptor (PDGFR) and fibroblast growth factor (FGF) and FGF receptor (FGFR) pathways, for example, provide potential escape mechanisms from anti‐VEGF/VEGFR therapy that could facilitate resumption of tumor growth. Accordingly, more recent treatments have focused on inhibiting multiple signaling pathways simultaneously. This comprehensive review discusses the limitations of inhibiting VEGF signaling alone as an antiangiogenic strategy, the importance of other angiogenic pathways including PDGF/PDGFR and FGF/FGFR, and the novel current and emerging agents that target multiple angiogenic pathways for the treatment of advanced solid tumors. Implications for Practice: Significant advances in cancer treatment have been achieved with the development of antiangiogenic agents, the majority of which have focused on inhibition of the vascular endothelial growth factor (VEGF) pathway. VEGF targeting alone, however, has not proven to be as efficacious as originally hoped, and it is increasingly clear that there are many interconnected and compensatory pathways that can overcome VEGF‐targeted inhibition of angiogenesis. Maximizing the potential of antiangiogenic therapy is likely to require a broader therapeutic approach using a new generation of multitargeted antiangiogenic agents. It is increasingly clear that there are many interconnected and compensatory pathways that can overcome vascular endothelial growth factor‐targeted inhibition of angiogenesis. Maximizing the potential of antiangiogenic therapy is likely to require a broader therapeutic approach using a new generation of multitargeted antiangiogenic agents.